Ultimum Remedium Terhadap Keterlibatan Notaris Dalam Perbuatan Melawan Hukum - Fairuzia, Halwa; Velentina, Rouli Anita (UI Scholars Hub, 2022)
Ultimum Remedium is a principle that means criminal sanctions should be the last resort in solving a problem, where civil and administrative sanctions are prioritised. In this journal, the researcher will discuss how this principle relates to the authority held by the Notary Honorary Council in limiting actions against the law committed by notaries. This study uses normative juridical research, where the law serves as a foundation for examining legal regulations related to legal issues regarding unlawful acts committed by notaries.